Platelets selectively enhance lymphocyte adhesion on subendothelial matrix under arterial flow conditions - Spectre, Galia; Zhu, Linjing; Ersoy, Maria; Hjemdahl, Paul; Savion, Naphtali; Varon, David; Li, Nailin (Thrombosis and Haemostasis, 2012)
Platelet adhesion at sites of cardiovascular injury may facilitate leukocyte deposition. We asked if and how platelets enhance lymphocyte adhesion on different subendothelial matrix protein (SEMP)-coated surface at arterial shear stress. Hirudinised whole blood was subjected to an arterial shear rate (500 s−1) in a Cone and Plate(let) analyser (CPA) for 5 minutes using plates coated with bovine serum albumin (BSA), collagen, fibrinogen, von Willebrand factor (vWF), or fibronectin. Platelet and lymphocyte adhesion were monitored by CPA and flow cytometry. Exposure of blood to collagen, fibrinogen, and vWF-coated surfaces induced platelet activation. The most marked effect was seen with collagen-coating, which markedly enhanced the adhesion of all lymphocyte subpopulations compared to BSA-coating. Fibrinogen-coating supported both T and NK cell adhesion, while vWF-coated surface only enhanced NK cell deposition. In contrast, fibronectin enhanced neither platelet activation nor lymphocyte adhesion. Moreover, platelets preferentially facilitated adhesion of large CD4+ and CD8+ T cells and NK cells, and of small B cells. Enhanced cell adhesion of larger lymphocytes was associated with elevated platelet conjugation and higher lymphocyte expression of PSGL-1, Mac-1, and CD40L. The enhancement of lymphocyte adhesion was totally platelet-dependent, and was abolished in platelet-depleted blood. Moreover, blockade of the platelet adhesion molecules P-selectin, GPIIb/IIIa, and CD40L attenuated platelet-dependent lymphocyte deposition. In conclusion, platelets support lymphocyte adhesion on SEMP-coated surfaces under arterial shear. The enhancement is selective for large T and NK cells and small B cells.
Keywords: Platelets; lymphocytes; arterial flow; subendothelial matrix proteins